2011
DOI: 10.2741/3869
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines as prognstic tool in breast carcinoma

Abstract: Serum cytokines are promising biomarkers of cancer staging and outcome prediction, including response to treatment. Serum samples were collected from 200 breast carcinoma patients prior to chemotherapy treatment. Luminex liquid protein chip technology was used to analyze 25 cytokines in serum. Linear regression was used to analyze the relationship of cytokine levels and tumor size. The independent sample T-test and Chi-square test methods were used to analyze the difference of cytokine levels between two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The major secretory characteristic of TAMs includes the production of interleukin-10 (IL-10), which is an immunosuppressive cytokine which participates in the growth and metastasis of different human malignant tumors. Sources of IL-10 include monocytes, a subtype of dendritic cells which activates macrophages and TAMs (10). IL-10 plays an important role in preventing inflammation in the negative feedback loop (11).…”
Section: Introductionmentioning
confidence: 99%
“…The major secretory characteristic of TAMs includes the production of interleukin-10 (IL-10), which is an immunosuppressive cytokine which participates in the growth and metastasis of different human malignant tumors. Sources of IL-10 include monocytes, a subtype of dendritic cells which activates macrophages and TAMs (10). IL-10 plays an important role in preventing inflammation in the negative feedback loop (11).…”
Section: Introductionmentioning
confidence: 99%
“…IL-10 is produced by monocytes, activated macrophages, and a subtype of dendritic cells (22). In cancers, additional sources of IL-10 include the alternatively activated M2 macrophages and TAMs (23,24). Because the major stimulus for the IL-10 expression is inflammation, IL-10 plays a major role in the negative feedback loop that prevents uncontrolled inflammation (25).…”
Section: Introductionmentioning
confidence: 99%
“…There was no statistically significant correlation between serum baseline levels of IL-6 and ER/PR/Her 2 neu status in our study. Lv et al [14] have reported significant differences in levels of serum IL-6 between different Her 2 groups in their study conducted in Chinese patients.…”
Section: Discussionmentioning
confidence: 88%